Sistem Pendukung Keputusan Seleksi Fasilitator Sumber Daya Manusia Menggunakan Metode Electre (Studi Kasus: Dinas Kesehatan Sibuhuan) - Daulay, Nur Hasanah; Nasution, Surya Darma; Fadlina, Fadlina (STMIK Budi Darma, 2020)
During this time the health department selected the facilitators by being selected directly by the Head of Human Resources, namely giving questions to the selected facilitators about health. The problem faced by the health department in conducting selection is that it is difficult to consider the facilitator's criteria due to different criteria. This is less effective because the evaluation of these criteria influences the expected selection results. In dealing with the problem of facilitator selection conducted by the Head of Human Resources, a decision support system can be built in dealing with the problem of selection of facilitators by using the ELECTRE method. Criteria that will be used as a facilitator's assessment such as ability, experience, education, creative, and discipline. For this reason, the author expects that the application of the facilitator selection decision support system to apply the ELECTRE method can facilitate health officials in the selection of facilitators